THE PRINCIPAL TRANSFORMATIONAL LEADERSHIP STYLES AND THEIR EFFECTS ON TEACHERS’ MOTIVATION - Phyu Thet Wai; Phongsatha, Thanawan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2024)
Purpose: The purpose of this paper is to identify the factors of principal transformational leadership styles effect on the level of teachers’ motivation in Private Institutes at Yangon Region. The research objectives were to examine the levels of principal transformational leadership style including idealized influence, inspirational motivation, intellectual stimulation and individualized consideration, teachers’ motivation and identify the factors of principal transformational leadership styles effect on the level of teachers’ motivation. The survey questionnaire was applied for data collection with 36 teachers from 3 private institutes participated as the respondents. Multiple Linear Regression was applied for data analysis. The results revealed that a transformational leadership has statistically significant influence on teachers’ motivation. The individualized influence was the strongest influence which was accounted for 39.3% of the variance in the teacher’s motivation and it was statistically significant at p <.001 with the Beta value of .701. In conclusion, this study recommends that principals should focus on individualized consideration factor that enhance the level of teachers’ motivation to increase effectiveness of private institutions at Yangon Region, Myanmar.